2019
DOI: 10.1039/c8fo02052c
|View full text |Cite|
|
Sign up to set email alerts
|

Housefly (Musca domestica) larvae powder, preventing oxidative stress injuryviaregulation of UCP4 and CyclinD1 and modulation of JNK and P38 signaling in APP/PS1 mice

Abstract: Housefly (Musca domestica) Larvae powder (HL) is rich in antioxidants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The mechanisms of insect neuroprotective effects include antioxidation [ 87 ], anti-inflammation [ 87 ], cell cycle inhibition [ 87 ], and apoptosis prevention [ 88 ], which can prevent neurodegenerative diseases (e.g., Alzheimer's disease) [ 87 ], Parkinson's disease [ 170 ], Amyotrophic lateral sclerosis [ 228 ], and epilepsy [ 174 ]. Venom immunotherapy is an effective treatment for systemic allergic reactions to Hymenoptera venom.…”
Section: Effects and Consequences Of Using Medicinal Insectsmentioning
confidence: 99%
“…The mechanisms of insect neuroprotective effects include antioxidation [ 87 ], anti-inflammation [ 87 ], cell cycle inhibition [ 87 ], and apoptosis prevention [ 88 ], which can prevent neurodegenerative diseases (e.g., Alzheimer's disease) [ 87 ], Parkinson's disease [ 170 ], Amyotrophic lateral sclerosis [ 228 ], and epilepsy [ 174 ]. Venom immunotherapy is an effective treatment for systemic allergic reactions to Hymenoptera venom.…”
Section: Effects and Consequences Of Using Medicinal Insectsmentioning
confidence: 99%
“…Remarkably, the antioxidant capacity of these insects is similar to foods recognized for their high antioxidant levels, such as cucumbers (2.8 mg TE/g), apples—golden delicious (2.2 mg TE/g)—and kiwifruit (2.7 mg TE/g) [ 58 ]. The high antioxidant capacity is associated with the presence of chitin, cuticle proteins, catalase, antibacterial peptides and superoxide dismutase, among others [ 59 ]. Therefore, insect meals could be included in diets as functional ingredients for promoting pet health.…”
Section: Reasons For Using Insects In Pet Foodmentioning
confidence: 99%
“…All scheduled experiments were carried out in the morning (8.00-9.00 am) to maintain uniformity with the experiments. The larval extract was dissolved in saline solution and administered orally by gavage using a gastric tube at the dose of 200 mg/kg/day (He, et al, 2019) [33]. Female rats were divided into experimental groups (10 female/each) as shown in the following design (synopsis):…”
Section: Groups Planningmentioning
confidence: 99%
“…Moreover, the larval extract has been reported to be associated with a variety of health therapy including hepatoprotective in hepatic damage induced by carbon tetrachloride in rats (Wang, et al, 2007) [26], antihepatitic B virus in a cell line (Lu, et al, 2014) [27], hyperlipidemia (Ai et al, 2008) [28], antitumor (Cao, et al, 2010) [29], antifungal (Fu, et al, 2009) [30], and anti-inflammatory (Chu, et al, 2011) [31], in addition to their capacity to ameliorate immunomodulatory proficiency (Cao, et al, 2012) [32]. Recent research has revealed that housefly larvae powder treatment increase protein activities of CAT, SOD, have a protective effect in memory deterioration and may inhibit oxidative stress-induced damage (He, et al, 2019) [33].…”
Section: Introductionmentioning
confidence: 99%